Linguistic Sign on The Meaning of Uliat Manyang Dance From South Siberut Mentawai - Aditiawarman, Mac; Tulia Sabojiat, Diana (Jurnal Ilmiah Pendidikan Scholastic, 2024)
This research discusses linguistic signs in the meaning of the Uliat Manyang dance movements from South Siberut, Mentawai. The Uliat Manyang dance is a dance that still functions in traditional ceremonies in Mentawai. The Uliat Manyang dance is a ritual in the form of a dance that imitates the movements of an eagle. The Uliat Manyang dance is performed by Sikerei at the Panunggru event, which is an important ceremony where the event marks the end of the mourning period and as a sign of eternal separation between the souls of the deceased and the families left behind. This dance was performed by Sikerei featuring vocal, facial and gesture elements. This research aims to determine the signifier and signified contained in the Uliat Manyang dance movements and the meaning of the song lyrics in the Uliat Manyang dance. Apart from that, this research also analyzes the body signs of Uliat Manyangdance movements. The theory used in this study is semiotics, which refers to the theory of linguistic signs proposed by Saussure in Candler. This study is a descriptive qualitative study in the form of field notes, observations, interviews, videos, and photos. The stages of implementation are carried out by observations made by watching dances at two events, recorded in video form. The conclusion in this analysis is that the Uliat Manyang dance is a dance that is a symbol of an animal that tells the story of the life of an eagle that is teased by a siamang, but they still maintain togetherness and do not cause quarrels with each other in living their lives. The story of the eagle and the siamang is told through movements and every song lyric. Likewise with the Mentawai people, they always live their daily lives together, such as farming, hunting together, and processing sago which is used as a staple food. Traditional Mentawai dance is a dance that has artistic, magical and mystical values ​​so that turuk laggai is believed to be a dance that intercedes for the spirits of ancestors and humans.